Conferencia. Food at work: workplace solutions tor malnutrition, obesity and chronic diseases - Christopher Wanjek (Universidad de Antioquía, 2010)
In my presentation, "Food at Work," I describe positive examples of how governments, employers and trade unions are improving the nutritional status of workers and subsequently improving productivity. My focus is global but with an emphasis on health concerns in Colombia and Latin America.